Long-term blood pressure variability and development of chronic kidney disease in type 2 diabetes. Issue 4 (April 2019) - Viazzi, Francesca; Bonino, Barbara; Mirijello, Antonio; Fioretto, Paola; Giorda, Carlo; Ceriello, Antonio; Guida, Pietro; Russo, Giuseppina T.; De Cosmo, Salvatore; Pontremoli, Roberto
Abstract : Objective: Long-term visit-to-visit SBP variability (VVV) has been shown to predict cerebro-cardiovascular events and end-stage renal disease in chronic kidney disease (CKD) patients. Whether SBP VVV is also a predictor of CKD development in diabetes is currently uncertain. We assessed the role of SBP VVV on the development of CKD in patients with type 2 diabetes (T2D) and hypertension in real life. Methods: Clinical records from 30 851 patients with T2D and hypertension, with normal estimated glomerular filtration rate (eGFR) and regular visits during a 4-year follow-up were analyzed. SBP variability was measured by three metrics: coefficient of variation; SD of the mean SBP and average absolute difference of successive values in each individual. CKD was defined as eGFR less than 60 and/or a reduction in eGFR at least 30% from baseline. Results: Over the 4-year follow-up, 9.7% developed eGFR less than 60 and 4.5% an eGFR reduction at least 30% from baseline. Several clinical characteristics (older age, male sex, SBP, DBP, albuminuria, glycated hemoglobin, insulin treatment) were related to intraindividual SBP variability. Patients with VVV in the upper quintile showed an increased risk of developing both components of CKD [adjusted odds ratio (OR) 1.21, P < 0.001 and 1.32, P < 0.001, respectively]. The multivariable adjusted ORs of SBP coefficient of variation quintiles 2–5 for the incidence of CKD were incrementally higher (OR 1.04, P = 0.601, OR 1.05, P = 0.520, OR 1.21, P < 0.017 and OR 1.42, P < 0.001 as compared with the first quintile). Conclusion: Increased long-term BP variability predicts CKD in patients with T2D and hypertension. Abstract : Supplemental Digital Content is available in the text